DOES ASSET OWNERSHIP REDUCE CHRONIC POVERTY? - A. Etim, Nsikak-Abasi; Edet, Glory E. (European Scientific Journal, ESJ, 2014)
Assets play an important role in the understanding of chronic poverty. This study was conducted in southern Nigeria to quantitatively assess the poverty level of households with respect to ownership of assets. Using the multistage sampling technique, primary data were obtained from 150 households with the aid of questionnaire. Data were subjected to analyses using the Foster Greer Thorbecke weighted poverty index and stochastic dominance analysis. Results indicate that poverty incidence, depth and severity was lower for households who own certain assets as land, houses, cars, motorcycles and sewing machines. The δ-value of the difference in the two sub-groups’ poverty incidences is significant (P < 0.01). Findings reveal that asset portfolio of majority of households was substantially low as more than 70 percent owned assets valued less than N100,000. Results of stochastic dominance analysis reveal that there was first order stochastic dominance. Result underscores the need to focus on poverty reduction policies that will increase the asset portfolio of rural households who are mostly dependent in farming for their income and food supplies